2014
DOI: 10.1021/ic500629y
|View full text |Cite
|
Sign up to set email alerts
|

Robust Molecular Crystals of Titanium(IV)-oxo-Carboxylate Clusters Showing Water Stability and CO2 Sorption Capability

Abstract: A series of new Ti(IV)-oxo clusters supported by carboxylate ligands are synthesized by solvothermal reactions, and their crystal structures and gas sorption properties are studied in detail. Depending on the reaction medium, two types of Ti6O6 clusters are formed with benzoate-derived ligands whose 2- or 4-position is substituted by a hydrophobic moiety. The molecular packing structures of these Ti clusters are found stable against water- and heat-treatments. Gas sorption studies reveal that a dense-packed Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 29 publications
(26 reference statements)
0
32
0
Order By: Relevance
“…70 POT cages, especially the structurally-diverse carboxylatemodified ones, are good candidates as gas adsorbents. 71 (Figure 15b) (with 33% solvent-accessible lattice void) loses its crystallinity. Although neither 32 nor 33 demonstrate any N 2 or CH 4 adsorption properties, a significant uptake of CO 2 at 195 K was observed for both compounds (Figure 15c,d), possibly due to the small kinetic diameter of CO 2 (ca.…”
Section: Gas Adsorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…70 POT cages, especially the structurally-diverse carboxylatemodified ones, are good candidates as gas adsorbents. 71 (Figure 15b) (with 33% solvent-accessible lattice void) loses its crystallinity. Although neither 32 nor 33 demonstrate any N 2 or CH 4 adsorption properties, a significant uptake of CO 2 at 195 K was observed for both compounds (Figure 15c,d), possibly due to the small kinetic diameter of CO 2 (ca.…”
Section: Gas Adsorptionmentioning
confidence: 99%
“…Such structural expansion is believed to be responsible for the distinct step in the adsorption branch of CO 2 for 35 ( Figure 16e). 71 Further studies have revealed that the substituents on the carboxylate ligands also play an important role in the adsorption of gaseous CO 2 . 71 By using relatively linear carboxylate ligands (e.g., 4-tbbz, Figure 16c), the intermolecular voids between adjacent ligands can be preserved or even enlarged.…”
Section: Gas Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diffraction quality crystals of each of the titanium compounds 5-8 were grown by vapour diffusion (5,6,8) or slow evaporation (7). Single crystal X-ray diffraction studies of 5-8 showed a common tetranuclear titanium complex Ti4(μ-O)2L4 (L = 1-4, Figure 1).…”
Section: Synthesis Of Ligands and Metal Complexesmentioning
confidence: 99%
“…The documented applications of POT cages include gas adsorption, photocatalytic water splitting, pollutant degradation, electrochemical water oxidation, dye‐sensitized solar cells, fluorescent labeling, and TiO 2 nanoparticle and thin film production . Despite these diverse applications, the potential of POT cages in the area of flexible materials has not so far been explored.…”
Section: Introductionmentioning
confidence: 99%